A GPU-based DEM-FEM computational framework for tire-sand interaction simulations. (15th October 2018) - Zheng, Zumei; Zang, Mengyan; Chen, Shunhua; Zeng, Haiyang
Highlights: A GPU-based discrete-finite element method is developed by using the CUDA FORTRAN. The effectiveness and scalability of the method are validated. The developed method is applied to tire-sand interaction simulations. A speedup of more than 15 is achieved in tire-sand interaction simulation. Simulation results of tire-sand interaction cases agree well with experimental results. Abstract: Recently, the discrete-finite element method (DEM-FEM) has proved to be an advanced technique for solid-particle interaction simulations. However, the low computational efficiency limits its applications to practical engineering problems. To achieve this end, this paper proposes a Graphics Processing Unit (GPU) based DEM-FEM, including contact detection, force calculation and information update, in the context of Compute Unified Device Architecture (CUDA) FORTRAN environment. Three numerical examples are performed to validate the efficiency, effectiveness and scalability of the developed method. On this basis, the GPU-based DEM-FEM is extended to a computing platform, and programmed into our in-house code PDFP-OVS for a typical solid-particle interaction problem, i.e. the running performance of a pneumatic tire on granular sand. Numerical result shows that a speedup of more than 15 can be achieved. The simulation results are found to be in good agreement with the experiment results in terms of the gross tractive effort, the drawbar pull and the running resistance, which validates the capacity of the platform in the travel performance analysis of the tire on granular sand.